Transurethral Treatment of a Seminal Vesicle Cyst With Lithiasis: Case Report - Mohamadhusni Zarli; Joao G. Porto; Ruben Blachman-Braun; Hemendra N. Shah (Case Reports in Surgery)
Seminal vesicle cyst (SVC) is a rare condition that can arise from congenital or acquired causes. In this report, we describe the case of a 33-year-old male who was incidentally discovered to have SVC and seminal vesicle stones following complaints of abdominal pain. He presented to the emergency department with these symptoms, which prompted further investigation and diagnosis. Computerized tomography (CT) scan revealed diverticulitis and a fluid attenuation lesion within the right aspect of the prostate gland. He was referred to urology, and further evaluation showed a right SVC of 1.8 × 1.5 × 1.5 cm on magnetic resonance imaging (MRI). The patient underwent endoscopic drainage of the SVC via transurethral seminal vesiculoscopy (TRU-SVS) and holmium laser incision. Three stones ranging from 2 to 4 mm were identified and removed with N-gage basket from the seminal vesicle resulting in successful removal of the stones and restoration of the ejaculatory duct’s patency. Follow-up visits showed resolution of pain and an improvement in semen volume. This case report highlights the importance of considering SVC as a differential diagnosis in male patients presenting with such symptoms. TRU-SVS is a feasible and effective treatment option for SVC and associated seminal vesicle stones.